Here's an out of the box solution that involves neither substitution nor elimination
x + y = 1
y*(y - x) = 0
Either y = 0 and x = 1
Or y-x = 0 ie y = x = 1/2
Solns: (1,0), (1/2, 1/2)
2007-10-22 06:19:35
·
answer #1
·
answered by Dr D 7
·
0⤊
0⤋
just substitue y = 1 -x into the 2nd equation.
(1-x)(1-x) - x(1-x) =0
Then solve the equation, watch out for the sign.
you ends up with
1-3x+2 x^2 = 0
(1-2x)(1-x) = 0
x = 1/2 or 1.
Then, you plug in the value of x to get the value of y
2007-10-22 13:41:09
·
answer #2
·
answered by modern wushu 2
·
0⤊
0⤋
Ans.
y ^2-xy=o
y^2=xy y=x but given y=1-x
so it is wrong.
2007-10-22 13:41:28
·
answer #3
·
answered by Sasi Kumar 4
·
0⤊
0⤋
(1 - x)² - x(1 - x) = 0
1 - 2x + x² - x + x² = 0
2x² - 3x + 1 = 0
(2x - 1)(x - 1) = 0
x = 1/2 , x = 1
y = 1/2 , y = 0
(1/2,1/2) , (1,0)
2007-10-22 13:41:17
·
answer #4
·
answered by Como 7
·
0⤊
0⤋